Primerjava izbranih krajinsko-ekoloških kazalcev za gozdove v dveh različnih krajinskih tipih - Pirnat, Janez (Acta silvae et ligni, 2015)
By analysing changes in landscape structure we can trace the influence they have on the evaluation of the diversity function of a forest. In the presented research, it was assessed which indices for computing areas, cores and aggregation tendencies that can be calculated with the Fragstats 4.2 programme best meet our needs, what limits they have and what we should pay special attention to. We considered differences in the resolution of incoming data and different rules for the calculation of raster cells. Both were compared for forests in two different landscape types: Kočevje and Slovenska Istra. The basic surface indices CA and PLAND proved to be the most suitable, while for more demanding purposes, AREA_AM can be used as well. For the evaluation of core areas, basic indices proved to be the most suitable, too, specifically TCA and CPLAND. Other important indices were the index of the number of core areas per surface unit DCAD and indices CORE_AM and DCORE_AM for a more detailed spatial evaluation of core areas, whereas most useful for the evaluation of aggregation tendency proved to be the patch density index PD.
Keywords: krajinsko-ekološki kazalci Fragstats; gozdovi; pestrostna funkcija